2015
DOI: 10.1038/cdd.2015.156
|View full text |Cite
|
Sign up to set email alerts
|

T-cell development of resistance to apoptosis is driven by a metabolic shift in carbon source and altered activation of death pathways

Abstract: We developed a model system to investigate apoptotic resistance in T cells using osmotic stress (OS) to drive selection of deathresistant cells. Exposure of S49 (Neo) T cells to multiple rounds of OS followed by recovery of surviving cells resulted in the selection of a population of T cells (S49 ) that failed to die in response to a variety of intrinsic apoptotic stimuli including acute OS, but remained sensitive to extrinsic apoptotic initiators. Genome-wide microarray analysis comparing the S49 (OS 4-25) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…T cells may mediate cell death by various mechanisms. Previous studies have demonstrated that Th17 cells may activate and induce cell death by Fas-mediated apoptosis, which is consistent with our results ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 94%
“…T cells may mediate cell death by various mechanisms. Previous studies have demonstrated that Th17 cells may activate and induce cell death by Fas-mediated apoptosis, which is consistent with our results ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 94%
“…They can activate caspases through a series of signal transduction, thus leading to the degradation of the nucleus and various substrates in the cytoplasm (32,33). Caspase-3 is the most common executor of the apoptosis pathway (34,35). The Bcl-2 family serves a critical role in regulating apoptosis, while ERK1/2 phosphorylation can achieve anti-apoptosis and promote proliferation through phosphorylating Bcl-2, activating transcriptional factors, and interfering TNF related apoptosis inducing ligand (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a Warburg-like mechanism also is operative in other rapidly proliferating cells and tissues ( e.g. , T-lymphocytes, embryonic tissues) [23] , [24] .…”
Section: The Warburg Effect: the Origin Of Metabolic Differences Betwmentioning
confidence: 99%